Hybrid Carbon Dioxide Reduction Photocatalysts Consisting of Macrocyclic Cobalt(III) Complexes Deposited on Semiconductor Surfaces. Issue 6 (4th March 2020) - Huang, Peipei; Pantovich, Sebastian A.; Okolie, Norbert O.; Deskins, N. Aaron; Li, Gonghu
Abstract: Hybrid photocatalysts can be prepared by coupling metal‐ligand complexes with light‐harvesting semiconductors. It is often challenging and time consuming to derivatize ligands with anchoring groups to effectively attach onto surfaces. In this study, we synthesized hybrid carbon dioxide reduction photocatalysts by directly depositing two macrocyclic Co(III) complexes on three different semiconductor surfaces (TiO2, N−Ta2 O5 and C3 N4 ). The resulting hybrid photocatalysts were characterized with various techniques and tested in CO2 reduction reactions under different light conditions. Excellent visible‐light CO2 ‐reduction activity was obtained using C3 N4 as the light‐harvesting semiconductor. Density functional theory calculations were conducted to help understand interactions between the cobalt complexes with a model TiO2 surface. Abstract : Drop and go : A series of hybrid photocatalysts have been prepared by directly depositing two macrocyclic cobalt(III) complexes on different semiconductor surfaces. [Co(HMD)Cl2 ]Cl showed stronger affinity than [Co(cyclam)Cl2 ]Cl with the semiconductors. In CO2 reduction under visible‐light irradiation, the hybrid photocatalyst prepared from [Co(HMD)Cl2 ]Cl and C3 N4 demonstrated the highest activity among all the hybrid photocatalysts prepared in this work.